2003
DOI: 10.1046/j.1365-2249.2003.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofMycobacterium tuberculosison differential activation of helper T-cells

Abstract: SUMMARYHost defence against tuberculosis infection involves T-lymphocyte mediated cellular immune responses. In this study we assessed T-cell activation by studying the early signal transduction events and production of cytokines by human CD4 + T-cells. The study constituted of five groups of subjects: ]i were seen in TB patients as compared to T + ve healthy controls. TB patients showed significantly lower levels of IL-2 and IFN g and higher levels of IL-4 as compared to normal healthy controls, suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The presence of intestinal worms may shift the immune background towards a Th2 profile as well as increased IL-10 producing Tregs (van den Biggelaar et al 2000) which may favour the establishment of mycobacterial infection and the development of active disease. Consistent with this explanation, other reports have shown that development of active TB is associated with enhanced Th2 type immune responses (Lienhardt et al 2002;Fincham et al 2003;Talreja et al 2003) and such responses are protective against helminth parasites (Turner et al 2003;Bradley & Jackson 2004;Jackson et al 2004). This would argue against the explanation that having active TB favoured infection with intestinal helminths.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The presence of intestinal worms may shift the immune background towards a Th2 profile as well as increased IL-10 producing Tregs (van den Biggelaar et al 2000) which may favour the establishment of mycobacterial infection and the development of active disease. Consistent with this explanation, other reports have shown that development of active TB is associated with enhanced Th2 type immune responses (Lienhardt et al 2002;Fincham et al 2003;Talreja et al 2003) and such responses are protective against helminth parasites (Turner et al 2003;Bradley & Jackson 2004;Jackson et al 2004). This would argue against the explanation that having active TB favoured infection with intestinal helminths.…”
Section: Discussionmentioning
confidence: 61%
“…2002; Fincham et al. 2003; Talreja et al. 2003) and such responses are protective against helminth parasites (Turner et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that M. tuberculosis [23] and M. leprae [16] curtails intracellular calcium levels which could be linked with reduced phagosome-lysosome fusion, thus for increased survival of M. tuberculosis in macrophages [24]. Interestingly, PBMCs from patients with mycobacterial infection have been reported to have reduced cytosolic [Ca +2 i concentrations [13,15,25] which could be due to inhibition in calcium mobilization across plasma membrane in lymphocytes by mycobacterial lipid antigens, as elucidated by series of calcium mobilization experiments performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms responsible for the differences are not known. Some studies have implied a phenotype shift of Th precursors to the Th2 type in patients with active TB and lower levels of IFN-␥ production (14,28,34,35). Stimulation with tuberculin in patients with active TB may induce T lymphocytes to express the early activation antigen but not to express IFN-␥ or to proliferate (6, 21).…”
Section: Discussionmentioning
confidence: 99%